Was Harrod Right? - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2012)
Modern growth theory derives mostly from Robert Solow's "A Contribution to the Theory of Economic Growth" (1956). Solow's own interpretation locates the origins of his "Contribution" in his view that the growth model of Roy Harrod implied a tendency toward progressive collapse of the economy. He formulates his view in terms of Harrod invoking a fixed-coefficients production function. This paper, first, challenges Solow's reading of Harrod, arguing that Harrod's object in providing a "dynamic" theory had little to do with the problem of long-run growth as Solow understood it, but instead addressed the medium run fluctuations. It was an attempt to isolate conditions under which the economy might tend to run below potential. In making this argument, Harrod does not appeal to a fixed-coefficients production function – or to any production function at all, as that term is understood by Solow. The paper next traces the history of the dominance of Solow's interpretation among growth economists. These tasks belong to the history of economics. The paper's final task belongs to economic history. It offers an informal reexamination of economic history through the lens of Harrod's dynamic model, asking whether there is a prima facie case in favor of Harrod's model properly understood.
Keywords: B22; O4; E12; E13; N1; B31; 330; economic growth; Roy Harrod; Robert Solow; dynamics; dynamic instability; knife-edge; warranted rate of growth; natural rate of growth